Development of a screening system for the evaluation of soybean [Glycine max] volatiles - Kakumyan, P.(Yamaguchi Univ. (Japan)); Kato, M; Hajika, M; Matsui, K (Bioscience, biotechnology, and biochemistry, 2009)
Flavor properties are important factors of soybean seeds in their utilization as food materials. In order to isolate novel varieties and mutants of soybean having preferable flavor properties, a simple and efficient screening system was established using an automated headspace sampler coupled to gas chromatography. With this system, five major volatile compounds were analyzed within 12 min. By applying this screening system to 626 soybean varieties collected worldwide, we isolated four soybean varieties that showed unique compositions of volatile compounds. Through biochemical analysis, it was found that the uniqueness of three of them was possibly independent of lipoxygenase enzyme, and thus perhaps this screening system can expand the subject of flavor properties beyond lipoxygenase and thus be useful in discovering new types of soybeans.